Survival of bronchopulmonary cancers according to radon exposure - Dessemon, Juliette; Perol, Olivia; Chauvel, Cécile; Noelle, Hugo; Coudon, Thomas; Grassot, Lény; Foray, Nicolas; Belladame, Elodie; Fayette, Jérôme; Fournie, Françoise; Swalduz, Aurélie; Neidhart, Eve-Marie; et al. (Frontiers in Public Health, 2024)
Introduction Residential exposure is estimated to be responsible for nearly 10% of lung cancers in 2015 in France, making it the second leading cause, after tobacco. The Auvergne-Rhône-Alpes region, in the southwest of France, is particularly affected by this exposure as 30% of the population lives in areas with medium or high radon potential. This study aimed to investigate the impact of radon exposure on the survival of lung cancer patients. Methods In this single-center study, patients with a histologically confirmed diagnosis of lung cancer, and newly managed, were prospectively included between 2014 and 2020. Univariate and multivariate survival analyses were carried out using a non-proportional risk survival model to consider variations in risk over time. Results A total of 1,477 patients were included in the analysis. In the multivariate analysis and after adjustment for covariates, radon exposure was not statistically associated with survival of bronchopulmonary cancers (HR = 0.82 [0.54–1.23], HR = 0.92 [0.72–1.18], HR = 0.95 [0.76–1.19] at 1, 3, and 5 years, respectively, for patients residing in category 2 municipalities; HR = 0.87 [0.66–1.16], HR = 0.92 [0.76–1.10], and HR = 0.89 [0.75–1.06] at 1, 3, and 5 years, respectively, for patients residing in category 3 municipalities). Discussion Although radon exposure is known to increase the risk of lung cancer, in the present study, no significant association was found between radon exposure and survival of bronchopulmonary cancers.